3D printing for development in the global south: the 3D4D challenge - Birtchnell, Thomas; Hoyle, William; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
Birtchnell and Hoyle explore how printers, designs, materials and infrastructures all need to be'just right' in order for meaningful social change to happen with appropriate scale. The 3D4D Challenge suggests 3D printing could reach scale in the Global South, even perhaps having the same impact as the mobile phone or microfinance in development.
Keywords: Social sciences; New business enterprises; Management